Metal casting : - Hurst, Steve (Intermediate Technology, 1996)
The book provides how to make equipment using local materials, and the various casting techniques. It includes green sand moulding - low-cost and relatively simple, encompassing different methods of sand casting appropriate to various types of product - and investment casting, which is an order, more versatile and precise technique but is more time-consuming. These and other methods are described and compared along with preparation and melting, fault finding and remedies, and kilns and furnaces